Flexible bronchoscopy combined with videolaryngoscope for tracheal intubation in a child with Hunter syndrome: a case report - Shamim, Faisal; Gulamani, Amber; Nisar, Abdullah; Rashid, Saima; Siddiqui, Humayun kaleem (Journal of the Pakistan Medical Association, 2023)
Hunter syndrome (mucopolysaccharidosis type II) has the highest reported prevalence of difficult tracheal intubation among the seven known types of mucopolysaccharidoses. Despite improved difficult airway guidelines and equipment, conventional approaches may fail in some cases. A 10-year-old child with Hunter syndrome, was scheduled for multiple dental extractions. On the first visit, failed intubation was declared as per Difficult Airway Society guidelines in the surgical day-care suite of our institute and the procedure was postponed. The case was then planned to be handled in the main operating room with additional preparation and input from the paediatric otolaryngologist for possible tracheostomy, paediatric intensive care for postoperative need for ventilation, and difficult airway resource faculty for an unconventional approach—videolaryngoscope combined with fibreoptic bronchoscope—which resulted in safe administration of anaesthesia. This case illustrates the importance of meticulous planning in the management of previously failed airway.